Effect Of Bobath Therapy On Extremity Muscle Strength In Post Stroke Infarced Patients - Hasina, Siti Nur; Cindy Fareza Maharani; Khamida; Andikawati Fitriasari; Rahmadaniar Aditya Putri (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2023)
Stroke is a disease that can cause weakness on one side of the body for sufferers, due to damage to the nervous system in the brain. One of the therapies to increase limb muscle strength in stroke patients is bobath therapy. This study aims to analyze the effect of bobath therapy on limb muscle strength in post-stroke infarction patients at RSI Jemursari Surabaya.The research design used a pre-experimental type with a one-group pre-post test design with a sample of 102 post-stroke infarction patient respondents using a non-probability sampling method with a purposive sampling technique. The independent variable in this study was bobath therapy, while the dependent variable was the muscle strength of the extremities of post-infarction stroke patients. The research instrument used an observation sheet containing a strength scale measuring instrument, namely the Manual Muscle Testing (MMT) score on measuring muscle strength with a score of 0-5. Data analysis used the Wilcoxon Signed Rank Test.The results of the study with the analysis of the Wilcoxon Signed Rank Test were obtained with a significance value of α = 0.05, ρ = 0.000, which means ρ <α, it can be concluded that H0 is rejected and H1 is accepted, which means that there is an effect of bobath therapy on limb muscle strength in postoperative patients. stroke infarction at RSI Jemursari Surabaya.Bobath therapy which was carried out 6 times within one month, and each movement was carried out for 3-5 minutes proved to be effective in increasing limb muscle strength in post-stroke infarction patients. It is hoped that bobath therapy can be applied by post-infarction stroke patients as a therapy to help increase limb muscle strength in accordance with Standard Operational Procedures.